Immunoexpression of matrix metalloproteinase‐2 and matrix metalloproteinase‐9 in the metastasis of squamous cell carcinoma of the human tongue - Zhou, CX; Gao, Y; Johnson, NW; Gao, J (Australian dental journal, 2010)
Background:  Squamous cell carcinoma of the tongue has frequent lymph node metastases and poor prognosis. Matrix metalloproteinase‐2 (MMP‐2) and matrix metalloproteinase‐9 (MMP‐9) are reported to degrade basement membrane, facilitating invasion and metastasis. This study determined the expression of MMP‐2/MMP‐9 in primary tongue cancer with or without cervical metastases and analysed the significance of such expression in relation to the presence or absence of metastases. Methods:  Expressions of MMP‐2/MMP‐9 were detected by immunohistochemistry in 10 specimens of normal oral mucosa, 20 lymph node‐negative tongue cancers, 41 lymph node‐positive tongue cancers and their metastasized tumours in cervical lymph nodes. Results:  MMP‐2/MMP‐9 expression was seldom found in normal epithelium. In lymph node‐negative tongue cancer, 45% and 40% of these primary tumours were positively stained for MMP‐2/MMP‐9, respectively. Importantly, in lymph node‐positive tongue cancer, 71% and 79% of these primary tumours were positive for MMP‐2/MMP‐9, respectively. Overexpression of MMP‐2/MMP‐9 was present in the metastatic lymph nodes. Conclusions:  Our results imply that MMP‐2 and/or MMP‐9 play an important role in invasion and metastasis in tongue cancer, and that analysis of MMP expression and/or activity in primary tumours may have a predictive value for the actual or potential presence of cervical metastases.